Improvement of lime production in shaft furnaces - Питак, Инна Вячеславовна; Шапорев, Павел Валерьевич; Шестопалов, Алексей Валерьевич; Шапорев, Валерий Павлович (Technology audit and production reserves, 2014)
The analysis of shaft furnaces for lime production is shown. The main disadvantages of modern furnaces during the lime burning with polydisperse composition are identified. It is proposed the design of overturning furnaces with high efficiency, which enhances the productivity of the furnace by 15 %, waste disposal carbonate raw materials, reduction of heat consumption by 20-28 %. The kinetic features of burning process were established in experimental researches. The data of furnace operation with the recommended design changes is given. The adopted in this work approach to process improvement and the design of the shaft furnace allowed developing a rational geometrical design of the shaft furnace reaction zone, and correlation of zone size from the particulate material fed to the burning, and the highest productivity, which is associated with the transverse dimension of the shaft. The relations obtained in the design of shaft lime-burning furnaces is an effective means of solving the problems of scaling of studied processes and objects, although they are semi-empirical. As shown from the table of the performance of the industrial shaft furnace and semi furnace with cone transitions given in this paper, the efficiency of lime burning in the simulated structure is evident.